GAMBARAN STRATEGI PENGADAAN SEDIAAN FARMASI APOTEK PUTRI GUMAYUN DI MASA PANDEMI COVID-19 - Dina Retnoningsih; Agus Susanto; Akhmad Aniq Barlian (Bhamada: Jurnal Ilmu dan Teknologi Kesehatan (E-Journal), 2022)
Drugs are an important component of health services, if there is a shortage of drugs in pharmacies, it will reduce the level of consumer confidence in these pharmacies. Proper management of pharmaceutical preparations can anticipate patient needs which are often unpredictable. Since the COVID-19 outbreak spread in Indonesia, the need for vitamins, supplements, fever-reducing drugs, cough, and cold medicines has experienced a massive and significant increase in sales. The research on the description of the strategy for the procurement of pharmaceutical preparations at the Putri Pharmacy during the COVID-19 pandemic is social pharmacy research with an observational (non-experimental) and qualitative descriptive research design. The subjects of this study were pharmacists in charge of pharmacies and TTK (pharmaceutical technical personnel) at Putri Pharmacy. This study is intended to clearly identify the strategy for the procurement of pharmaceutical preparations at the Putri Pharmacy in Gumayun during the COVID-19 pandemic. Through this research, we get an overview of the procurement strategy of Putri Pharmacy. Activity the most important thing is to find information as quickly as possible about needed drugs. Besides that, it is necessary now order with the number of goods improved. For the last need build good relationships with the pharmaceutical wholesaler (PBF) as supporting factors.